Erythropoietin as banned substance in professional sports: effects on maximal aerobic capacity, endurance and detection methods - a review - Aghadi, Artur; Dybała, Ewelina; Cuber, Iwona; Mazurek, Magdalena; Białowąs, Edyta (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Erythropoietin (Epo) and its analogs used as performance-enhancing substance and are considered doping and are therefore forbidden in sports, however the scientific evidence behind doping is frequently weak. We aimed to determine the effects erythropoietin on maximal aerobic capacity(VO₂ max), endurence and to present direct detection methods. State of knowledge: Erythropoietin is a glycoprotein cytokine. During cellular hypoxia, Epo is secreted mainly by the kidneys, it stimulates bone marrow production of red blood cells. To compensate for normal red cell turnover, low levels of Epo are constantly secreted in sufficient quantities. In addition to anemia and chronic lung disease, cellular hypoxia can result in elevated levels of Epo. VO₂ max is the peak volume of oxygen that a person can consume during exercise. Essential for breathing, oxygen is inhaled by the lungs and converted into energy, which then fuels human cells and expels carbon dioxide in the exhaled breath. This allows the body to manage more efficiently aerobic workouts that involve a large amount of oxygen intake, such as running, swimming or other cardio exercises. Conclusions: Current data from PubMed indicate a significant relationship between Epo overuse and endurance in professional sports. That is one of the most important reasons to pay attention to the effects of EPO and new detection methods.